Solar cell and preparation method and application thereof
By setting a dielectric thin film layer on the surface of the copper electrode, the problem of copper electrode oxidation in traditional copper plating processes is solved, interface damage and electrical performance are improved, and the power of solar cell modules is improved.
Patent Information
- Application Number
- CN202411604772.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-25
AI Technical Summary
Traditional copper electroplating technology can easily lead to copper electrode oxidation in high temperature and high humidity environments, causing interface damage and inaccurate current-voltage performance testing, thereby reducing the power of solar cell modules.
A dielectric film layer is provided on the surface of the copper electrode. The thickness of the dielectric film layer is 30 nm-100 nm, selected from the group consisting of silicon nitride layer, silicon oxide layer or silicon oxynitride layer, and has a porosity of 30%-70% and a pore size of 30nm-80 nm.
The dielectric thin film layer not only improves interface damage and improves solar cell performance, but also protects copper electrodes, avoids oxidation, and improves the welding contact effect and power of the components.
Smart Images

Figure CN119698123A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a solar cell and a preparation method and application thereof. Background Art
[0002] Copper electroplating technology has attracted extensive attention as one of the mainstream technologies for reducing the cost of solar cell metallization in the future. However, the traditional copper electroplating process still has some problems, which prevents it from being put into mass production. The main problems include: (1) Traditional copper electroplating involves more wet chemical processes, which will cause certain corrosion damage to the battery, especially for the indium tin oxide (ITO) grain boundary in the heterojunction battery. This process requires high chemical corrosion resistance of ITO; (2) Since the copper electrode itself is easily oxidized in a high temperature and high humidity environment, especially the copper electrode after electroplating needs to undergo heat treatment and light injection. This process will cause large-area oxidation of the copper electrode. The formed oxide layer will lead to inaccuracy in the current-voltage (IV) performance test and poor contact of the component welding, thereby reducing the power of the solar cell module.
[0003] Therefore, the existing solar cell structure not only has the problem of interface damage during light injection, but also cannot avoid copper electrode oxidation. Summary of the invention
[0004] Based on this, it is necessary to provide a solar cell and a preparation method and application thereof to address the above problems; the solar cell structure can not only maintain the interface performance, but also avoid copper electrode oxidation, thereby improving the electrical performance of the solar cell and its components.
[0005] A solar cell comprises a silicon substrate and a passivation contact structure stacked on at least one surface of the silicon substrate, wherein a copper electrode is provided in a partial area of the surface of the passivation contact structure, and the copper electrode forms an ohmic contact with the passivation contact structure. The solar cell further comprises a dielectric film layer, and the dielectric film layer is provided on the surfaces of the passivation contact structure and the copper electrode.
[0006] In one embodiment, the dielectric film layer satisfies at least one of the following conditions:
[0007] (1) The thickness of the dielectric film layer is 30nm-100nm;
[0008] (2) The dielectric film layer is at least one layer selected from a silicon nitride layer, a silicon oxide layer, and a silicon oxynitride layer;
[0009] (3) The porosity of the dielectric film layer is 30%-70%, and the pore size is 30nm-80nm.
[0010] In one of the embodiments, a transparent conductive film layer is further provided on the surface of the passivation contact structure, the copper electrode is arranged on a partial area of the surface of the transparent conductive film layer, the copper electrode forms an ohmic contact with the transparent conductive film layer, and the dielectric film layer is arranged on the surface of the transparent conductive film layer and the copper electrode.
[0011] In one embodiment, the transparent conductive film layer satisfies at least one of the following conditions:
[0012] (1) The thickness of the transparent conductive film layer is 30nm-50nm;
[0013] (2) The material of the transparent conductive film layer is selected from at least one of indium tin oxide, indium zinc oxide, indium tungsten oxide, and stannous oxide.
[0014] In one embodiment, the solar cell includes a silicon substrate, the silicon substrate having a light-receiving surface and a backlight surface arranged in opposite directions, the light-receiving surface includes an intrinsic amorphous silicon layer, an N-type doped layer, and a transparent conductive film layer stacked from the inside to the outside, and the backlight surface includes an intrinsic amorphous silicon layer, a P-type doped layer, and a transparent conductive film layer stacked from the inside to the outside;
[0015] A copper electrode is provided in a partial area on the surface of the transparent conductive film layer, and the copper electrode forms an ohmic contact with the transparent conductive film layer. The dielectric film layer is arranged on the surface of the transparent conductive film layer and the copper electrode.
[0016] A method for preparing a solar cell comprises the following steps:
[0017] Passivating and doping the silicon wafer to form a passivated contact structure, and then preparing a copper electrode on the passivated contact structure;
[0018] A dielectric film layer is prepared on the surface of the copper electrode, and then annealing and light injection treatment are performed to obtain a solar cell.
[0019] In one embodiment, the dielectric film layer satisfies at least one of the following conditions:
[0020] (1) The thickness of the dielectric film layer is 30nm-80nm;
[0021] (2) The dielectric film layer is at least one layer selected from a silicon nitride layer, a silicon oxide layer, and a silicon oxynitride layer.
[0022] In one embodiment, a transparent conductive film layer is first deposited on the passivation contact structure, and then a copper electrode is prepared, wherein the transparent conductive film layer satisfies at least one of the following conditions:
[0023] (1) The thickness of the transparent conductive film layer is 30nm-50nm;
[0024] (2) The material of the transparent conductive film layer is selected from at least one of indium tin oxide, indium zinc oxide, indium tungsten oxide, and stannous oxide.
[0025] In one of the embodiments, the light injection treatment is performed by photothermal assistance, wherein the light source is an infrared laser, the light intensity is 8 suns-40 suns, and the time is 25s-180s.
[0026] In one embodiment, the light injection process includes a first light injection step, a second light injection step, a third light injection step, and a fourth cooling step, and the light injection process satisfies at least one of the following conditions:
[0027] (1) The light intensity of the second light injection step is greater than the light intensity of the first light injection step, and the light intensity of the second light injection step is greater than the light intensity of the third light injection step;
[0028] (2) The time of the second light injection step is shorter than the time of the first light injection step, and the time of the second light injection step is shorter than the time of the third light injection step;
[0029] (3) The temperature of the second light injection step is greater than the temperature of the third light injection step.
[0030] In one of the embodiments, the light injection process satisfies at least one of the following conditions:
[0031] (1) The light intensity of the first step light injection is 8 suns-18 suns, and the time is 5s-20s;
[0032] (2) The light intensity of the second light injection is 18 suns-40 suns, the time is 1 s-10 s, and the temperature is 180°C-260°C;
[0033] (3) The light intensity of the third step light injection is 8 suns-18 suns, the time is 10 s-60 s, and the temperature is 160°C-240°C;
[0034] (4) The cooling time in the fourth step is 10s-60s.
[0035] A photovoltaic module comprises the solar cell described above.
[0036] The solar cell structure of the present invention provides a dielectric film layer on the surface of the copper electrode. On the one hand, because the dielectric film layer contains a certain amount of hydrogen, it can passivate the ITO grain boundary and the crystalline silicon layer corroded by the copper electroplating chemical solution under light injection conditions, improve interface damage, and enhance the performance of the solar cell; on the other hand, the dielectric film layer can protect the copper electrode, so that the copper electrode is prevented from being oxidized during the light injection process, which is beneficial to improving the welding contact effect of the solar cell module, thereby improving the module power. In addition, providing a dielectric film layer on the surface of the copper electrode is also beneficial to reducing optical reflection and enhancing the light absorption capacity, thereby improving the spectral response of the battery and improving the conversion efficiency of the battery.
[0037] Therefore, the solar cell structure of the present invention can not only maintain the interface performance, but also avoid the oxidation of the copper electrode, thereby improving the electrical performance of the solar cell and its components. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 A schematic diagram of the structure of a solar cell in one embodiment of the present invention;
[0040] Figure 2 Schematic diagram of a process for preparing a solar cell according to one embodiment of the present invention.
[0041] Among them, 10, silicon substrate; 20, intrinsic amorphous silicon layer; 30, N-type doped layer; 40, P-type doped layer; 50, transparent conductive film layer; 60, dielectric film layer; 70, copper electrode. DETAILED DESCRIPTION
[0042] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0044] The present invention provides a solar cell, comprising a silicon substrate and a passivation contact structure stacked on at least one surface of the silicon substrate, wherein a copper electrode is provided in a partial area of the surface of the passivation contact structure, and the copper electrode forms an ohmic contact with the passivation contact structure. The solar cell also comprises a dielectric film layer, and the dielectric film layer is arranged on the surfaces of the passivation contact structure and the copper electrode.
[0045] By setting a dielectric film layer on the surface of the copper electrode, on the one hand, since the dielectric film layer contains a certain amount of hydrogen, it can passivate the ITO grain boundary and the crystalline silicon layer corroded by the copper electroplating chemical solution under light injection conditions, improve interface damage, and enhance the performance of solar cells; on the other hand, the dielectric film layer can protect the copper electrode and prevent the copper electrode from being oxidized during the light injection process, which is beneficial to improving the welding contact effect of the solar cell module, thereby increasing the module power. In addition, setting a dielectric film layer on the surface of the copper electrode is also beneficial to reducing optical reflection and improving the light absorption capacity, thereby improving the spectral response of the battery and improving the conversion efficiency of the battery.
[0046] Preferably, the thickness of the dielectric film layer is 30 nm-100 nm, including but not limited to any value among 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 100 nm or a range between any two values.
[0047] Specifically, the dielectric film layer is selected from at least one of a silicon nitride layer, a silicon oxide layer, and a silicon oxynitride layer, that is, the dielectric film layer can be a silicon nitride layer, a silicon oxide layer, a silicon oxynitride layer, or a composite layer formed by stacking at least two of the silicon nitride layer, the silicon oxide layer, and the silicon oxynitride layer.
[0048] In one embodiment, the dielectric film layer has a porous sparse structure, at least in the area located on the surface of the copper electrode, which is beneficial to ensure that when the battery is welded, the solder strip components can form good ohmic contact with the electrode through the porous channel structure.
[0049] Preferably, the porosity of the dielectric film layer is 30%-70%, including but not limited to any value among 30%, 40%, 50%, 60%, 70% or any range between two values; the pore size is 30nm-80nm, including but not limited to any value among 30nm, 40nm, 50nm, 60nm, 70nm, 80nm or any range between two values.
[0050] In one embodiment, a transparent conductive film layer is further provided on the surface of the passivation contact structure, the copper electrode is arranged on a partial surface area of the transparent conductive film layer, the copper electrode forms an ohmic contact with the transparent conductive film layer, and the dielectric film layer is arranged on the surface of the transparent conductive film layer and the copper electrode.
[0051] Preferably, the thickness of the transparent conductive film layer is 30 nm-50 nm, including but not limited to any value among 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or a range between any two values.
[0052] Specifically, the material of the transparent conductive film layer includes but is not limited to at least one of indium tin oxide (ITO), indium zinc oxide (IZO), indium tungsten oxide (IWO), and stannous oxide (SnO).
[0053] Preferably, the solar cell includes but is not limited to a heterojunction cell, and is preferably a heterojunction cell.
[0054] Combination Figure 1 As shown, it is a schematic diagram of the structure of a solar cell in one embodiment of the present invention, the solar cell includes a silicon substrate 10, the silicon substrate 10 has a light-receiving surface and a backlight surface arranged opposite to each other, the light-receiving surface includes an intrinsic amorphous silicon layer 20, an N-type doped layer 30, and a transparent conductive film layer 50 stacked from the inside to the outside, and the backlight surface includes an intrinsic amorphous silicon layer 20, a P-type doped layer 40, and a transparent conductive film layer 50 stacked from the inside to the outside.
[0055] A copper electrode 70 is disposed on a portion of the surface of the transparent conductive film layer 50 . The copper electrode 70 forms an ohmic contact with the transparent conductive film layer 50 . The dielectric film layer 60 is disposed on the surfaces of the transparent conductive film layer 50 and the copper electrode 70 .
[0056] It can be understood that at least one of the light-receiving surface and the backlight surface is a velvet surface.
[0057] Combination Figure 2 As shown, a method for preparing a solar cell provided by the present invention comprises:
[0058] S1, passivating and doping a silicon wafer to form a passivated contact structure, and then preparing a copper electrode on the passivated contact structure;
[0059] S2, preparing a dielectric film layer on the surface of the copper electrode, and then performing annealing and light injection treatment to obtain a solar cell.
[0060] In step S1, the present invention does not limit the passivation and doping treatment methods, and conventional processes in the art can be used. It is understandable that different passivation and doping treatment methods can be used for different types of solar cells to form different passivation contact structures. For example, the passivation contact structure in the tunneling oxide layer passivation contact cell includes a tunneling oxide layer and a doped polysilicon layer; the passivation contact structure in the heterojunction cell includes an intrinsic amorphous silicon layer and a doped layer.
[0061] In one embodiment, the silicon wafer is first subjected to texturing treatment before passivation.
[0062] In one embodiment, when preparing a heterojunction battery, it is preferred to first deposit a transparent conductive film layer on the passivation contact structure and then prepare a copper electrode. Further preferably, the thickness of the transparent conductive film layer is 30nm-50nm, including but not limited to any point value among 30nm, 35nm, 40nm, 45nm, 50nm or any range value between two of them.
[0063] Specifically, the material of the transparent conductive film layer includes but is not limited to at least one of indium tin oxide (ITO), indium zinc oxide (IZO), indium tungsten oxide (IWO), and stannous oxide (SnO); the preparation process of the transparent conductive film layer includes but is not limited to plasma enhanced chemical vapor deposition (PECVD).
[0064] In one embodiment, the copper electrode has a width of 10 μm-20 μm and a height of 5 μm-15 μm.
[0065] In one embodiment, the copper electrode is wet-plated, and the steps of wet-plating the copper electrode include: first preparing a seed layer, then forming a wet film on the surface of the seed layer and curing and drying it, and then electroplating the copper electrode after patterning, wherein the seed layer serves as a cathode in the electroplating process, and under the condition of power on, the Cu in the solution 2+ It obtains electrons at the cathode, is reduced to Cu and deposited onto the seed layer of the cathode, thus forming a copper electrode.
[0066] It should be noted that the present invention does not limit the specific process of patterning, and conventional processes in the art may be used, for example: exposing the wet film after curing and drying, and then forming the electrode pattern to be produced in a developer.
[0067] Preferably, the material of the seed layer includes but is not limited to at least one of silver, copper and tin. Further preferably, the thickness of the seed layer is 80nm-150nm, including but not limited to any point value among 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm or a range value between any two of them.
[0068] Preferably, the thickness of the wet film is 10 μm-30 μm, including but not limited to any value among 10 μm, 15 μm, 20 μm, 25 μm, 30 μm or any range between two values.
[0069] It should be noted that the present invention does not limit the preparation process of the wet film, and conventional processes in the art may be used, for example, the wet film is formed by screen printing, scraping or coating.
[0070] Preferably, the curing temperature is 80°C-120°C and the curing time is 5min-15min.
[0071] Preferably, the exposure method includes but is not limited to laser direct writing or UV exposure, wherein the wavelength of the light source includes but is not limited to 325nm, 350nm or 405nm.
[0072] Preferably, the developer includes but is not limited to at least one of potassium carbonate solution (K2CO3), sodium carbonate solution (Na2CO3), potassium bicarbonate solution (KHCO3), and sodium bicarbonate solution (NaHCO3). Further preferably, the mass concentration of the solute in the developer is 5%-10%.
[0073] Preferably, after the copper electrode is obtained by electroplating, a strong alkaline solution is used to remove the residual wet film, and the main component is preferably potassium hydroxide (KOH) or sodium hydroxide (NaOH); an acidic solution is used to remove the residual seed layer, and the main component is preferably sulfuric acid.
[0074] In step S2, a dielectric film layer is first prepared on the surface of the copper electrode, and then annealing and light injection treatment are performed. On the one hand, since the dielectric film layer contains a certain amount of hydrogen, the crystalline silicon layer corroded by the copper electroplating chemical solution can be passivated under light injection conditions, thereby improving interface damage and enhancing the performance of solar cells. This is especially true for heterojunction cells. Since the transparent conductive film in the heterojunction cell will form a polycrystalline state during the growth process, there will be gaps between different grains, and the bonding energy between atoms in the gaps is low. In the wet chemical process, the gaps will be corroded due to the low potential energy. The dielectric film layer material deposited later can cover the corroded area, and at the same time, the hydrogen in the dielectric film layer material can form bridge bonds with the elements, thereby achieving passivation.
[0075] On the other hand, the dielectric film layer can protect the copper electrode and prevent it from being oxidized during the light injection process, which is not only beneficial to improve the welding contact effect of the solar cell module, thereby increasing the module power, but also does not require the addition of an additional tin protective layer or high-cost oxygen-free equipment, nor does it require post-treatment of copper deoxidation. In addition, preparing a dielectric film layer on the surface of the copper electrode is also beneficial to reduce optical reflection and enhance the light absorption capacity, thereby improving the spectral response of the battery and improving the conversion efficiency of the battery.
[0076] Preferably, the thickness of the dielectric film layer is 30 nm-80 nm, including but not limited to any value among 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm or a range between any two values.
[0077] Specifically, the dielectric film layer is selected from at least one of a silicon nitride layer, a silicon oxide layer, and a silicon oxynitride layer, that is, the dielectric film layer can be a silicon nitride layer, a silicon oxide layer, a silicon oxynitride layer, or a composite layer formed by stacking at least two of the silicon nitride layer, the silicon oxide layer, and the silicon oxynitride layer.
[0078] It should be noted that the present invention does not limit the specific process of the dielectric film layer, and conventional processes in the art can be used. For example, the dielectric film layer is preferably prepared by PECVD. The density of the film can be adjusted by changing the RF power, pressure, deposition temperature, and gas flow ratio, so that the prepared dielectric film layer has a porous sparse structure, and there are conductive channels in the dielectric film layer, so that during the welding process, after the soldering strip is tinned, the tin can enter these conductive channels and contact the copper electrode, thereby not affecting the conductivity of the copper electrode. It is understandable that the present invention can also use other methods to prepare the dielectric film layer. When the prepared dielectric film layer has a certain density, the dielectric film material covering the surface of the copper electrode can be removed by grooving or the like to reduce the influence of the dielectric film material on the conductivity of the copper electrode.
[0079] Preferably, in a heterojunction battery, the dielectric film layer and the transparent conductive film layer form a laminated anti-reflection film, which is beneficial to further reduce optical reflection and enhance the light absorption capacity, thereby improving the spectral response of the battery, and further improving the conversion efficiency of the copper electroplating battery. In addition, the dielectric film layer is also beneficial to reduce the thickness of the transparent conductive film layer, thereby reducing costs.
[0080] In one embodiment, the light injection treatment preferably adopts a photothermal-assisted method, wherein the light source includes but is not limited to infrared laser, preferably infrared laser, and further preferably, the light intensity of the infrared laser is 8s-40s, and the time is 25s-180s.
[0081] In one embodiment, the light injection process includes a first light injection step, a second light injection step, a third light injection step, and a fourth cooling step.
[0082] Preferably, the light intensity of the second light injection step is greater than that of the first light injection step, and the light intensity of the second light injection step is greater than that of the third light injection step, so that during the light injection process, the light intensity shows a control trend of first increasing and then decreasing.
[0083] Preferably, the time of the second light injection step is shorter than that of the first light injection step, which in turn is shorter than that of the third light injection step. By regulating the time of light injection in each step and coordinating the change in light intensity, it is beneficial to reduce the problem of internal heat accumulation in the battery caused by high light intensity, thereby reducing the impact of the light injection process on battery efficiency performance.
[0084] Preferably, the temperature of the second light injection step is greater than the temperature of the third light injection step.
[0085] Further preferably, the light intensity of the first light injection is 8suns-18suns, including but not limited to any point value among 8suns, 10suns, 12suns, 15suns, 16suns, 17suns, 18suns or any range value between two of them; the time is 5s-20s, including but not limited to any point value among 5s, 8s, 10s, 12s, 15s, 16s, 18s, 20s or any range value between two of them. It is understandable that the present invention does not limit the temperature of the first light injection, and the temperature gradually increases from room temperature with the first light injection.
[0086] Further preferably, the light intensity of the second step light injection is 18suns-40suns, including but not limited to any value among 18suns, 20suns, 25suns, 30suns, 35suns, 40suns or a range between any two of them; the time is 1s-10s, including but not limited to any value among 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s or a range between any two of them; the temperature is 180℃-260℃, including but not limited to any value among 180℃, 200℃, 210℃, 220℃, 230℃, 250℃, 260℃ or a range between any two of them.
[0087] Further preferably, the light intensity of the third step light injection is 8suns-18suns, including but not limited to any value among 8suns, 10suns, 12suns, 15suns, 16suns, 17suns, and 18suns, or a range between any two of them; the time is 10s-60s, including but not limited to any value among 10s, 15s, 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, and 60s, or a range between any two of them; the temperature is 160℃-240℃, including but not limited to any value among 160℃, 180℃, 200℃, 210℃, 220℃, 230℃, and 240℃, or a range between any two of them.
[0088] More preferably, the cooling time in the fourth step is 10s-60s.
[0089] It is understandable that, under the premise that the light intensity of the second light injection is greater than that of the first light injection and the light intensity of the second light injection is greater than that of the third light injection, the light intensity of the first light injection, the light intensity of the second light injection and the light intensity of the third light injection will not be 18 suns at the same time.
[0090] Annealing can remove stress inside the copper electrode. In addition, for heterojunction cells, annealing can also crystallize and activate carriers in the transparent conductive film. Preferably, the annealing is performed by thermal curing at a temperature of 180°C-200°C for 10 min-20 min.
[0091] The present invention also provides a photovoltaic module, comprising the solar cell described above. The photovoltaic module can be widely used in multiple fields such as power generation, outdoor lighting, mobile power supply, and aerospace.
[0092] The solar cell and its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0093] Example 1
[0094] After the silicon wafer is textured, an amorphous passivation layer and a doping layer are formed on the surface. Then, a transparent conductive film layer is formed on the surface of the doping layer by PVD, and a seed layer is formed on the surface of the transparent conductive film layer. The material of the transparent conductive film layer is ITO with a thickness of 30nm; the material of the seed layer is copper with a thickness of 100nm. A wet film is formed on the surface of the seed layer by screen printing and cured and dried. The thickness of the wet film is 10μm, the curing temperature is 80℃, and the time is 15min. The surface of the wet film after curing and drying is exposed graphically by laser direct writing, and a pattern is formed in an alkaline developer. The wavelength of the light source is 325nm, and the developer is a K2CO3 solution with a concentration of 5%. Copper grid lines are electroplated on the pattern. The width of the grid lines is 20μm and the height is 15μm. KOH is used to remove the wet film, and sulfuric acid is used to remove the seed layer.
[0095] A dielectric film layer is formed on the surface of a transparent conductive film layer and a copper grid line by PECVD, wherein the dielectric film layer is silicon oxide, has a thickness of 50nm, a porosity of 70%, and a pore size of 30nm; then annealing and light injection treatment are performed, wherein the copper grid line is annealed by thermal curing, the annealing temperature is 180°C, and the time is 20min; the light injection adopts a photothermal-assisted method, and an infrared laser is used for step-by-step light injection treatment, wherein the first step adopts 8 suns conditions and irradiates for 20s, the second step adopts 18 suns conditions and irradiates for 10s, and the temperature is controlled at 180°C, the third step adopts 8 suns conditions and irradiates for 30s, auxiliary heating, and the temperature is controlled at 230°C, and the fourth step stops the light irradiation and naturally cools to room temperature, and the time is controlled at 60s to obtain a heterojunction battery.
[0096] Example 2
[0097] After the silicon wafer is textured, an amorphous passivation layer and a doping layer are formed on the surface. Then, a transparent conductive film layer is formed on the surface of the doping layer by PVD, and a seed layer is formed on the surface of the transparent conductive film layer. The material of the transparent conductive film layer is IZO with a thickness of 50nm; the material of the seed layer is silver with a thickness of 80nm. A wet film is formed on the surface of the seed layer by scraping and cured and dried. The thickness of the wet film is 15μm, the curing temperature is 100℃, and the time is 10min. The surface of the wet film after curing and drying is exposed graphically by UV exposure, and a pattern is formed in an alkaline developer. The wavelength of the light source is 365nm, and the developer is a Na2CO3 solution with a concentration of 8%. Copper grid lines are electroplated on the pattern. The width of the grid lines is 15μm and the height is 10μm. NaOH is used to remove the wet film, and sulfuric acid is used to remove the seed layer.
[0098] A dielectric film layer is formed on the surface of a transparent conductive film layer and a copper grid line by PECVD, wherein the dielectric film layer is a composite film layer of a silicon nitride layer and a silicon oxide layer, the thickness of the silicon nitride layer and the silicon oxide layer are 20 nm and 30 nm respectively, the porosity of the composite film layer is 50%, and the pore size is 50 nm; then annealing and light injection treatment are performed, wherein the copper grid line is annealed by thermal curing, the annealing temperature is 200° C., and the time is 10 min; the light injection adopts a photothermal assisted method, and an infrared laser is used for step-by-step light injection treatment, the first step adopts 18 suns conditions, irradiation for 20 seconds, the second step adopts 40 suns conditions, irradiation for 5 seconds, and the temperature is controlled at 250° C., the third step adopts 15 suns conditions, irradiation for 40 seconds, no auxiliary heating, and the temperature is controlled at 220° C. The fourth step stops the light irradiation, and naturally cools to room temperature for 50 seconds to obtain a heterojunction battery.
[0099] Example 3
[0100] After the silicon wafer is processed by texturing, an amorphous passivation layer and a doping layer are formed on the surface. Then, a transparent conductive film layer is formed on the surface of the doping layer by PVD, and a seed layer is formed on the surface of the transparent conductive film layer. The material of the transparent conductive film layer is SnO with a thickness of 40nm; the material of the seed layer is Sn with a thickness of 100nm. A wet film is formed on the surface of the seed layer by coating and cured and dried. The thickness of the wet film is 20μm, the curing temperature is 100℃, and the time is 15min. The surface of the wet film after curing and drying is exposed graphically by laser direct writing, and a pattern is formed in an alkaline developer. The wavelength of the light source is 405nm, and the developer is a mixed solution of Na2CO3 and NaHCO3, wherein the concentrations of Na2CO3 and NaHCO3 are both 5%. Copper grid lines are electroplated on the pattern. The width of the grid line is 20μm and the height is 15μm. NaOH is used to remove the wet film, and sulfuric acid is used to remove the seed layer.
[0101] A dielectric film layer is formed on the surface of a transparent conductive film layer and a copper grid line by PECVD, wherein the dielectric film layer is a composite film layer of a silicon nitride layer, a silicon oxide layer and a silicon oxynitride layer, the thicknesses of the silicon nitride layer, the silicon oxide layer and the silicon oxynitride layer are 5nm, 10nm and 30nm respectively, the porosity of the composite film layer is 40%, and the pore size is 60nm; then annealing and light injection treatment are performed, wherein the copper grid line is annealed by thermal curing, the annealing temperature is 190°C, and the time is 15min; the light injection adopts a photothermal assisted method, and an infrared laser is used for step-by-step light injection treatment, the first step adopts 8suns conditions for irradiation for 20s, the second step adopts 30suns conditions for irradiation for 5s, and the temperature is controlled at 230°C, the third step adopts 15suns conditions for irradiation for 20s, no auxiliary heating, and the temperature is controlled at 200°C, and the fourth step stops the light irradiation, naturally cools to room temperature, and the time is controlled at 10s to obtain a heterojunction battery.
[0102] Example 4
[0103] After the silicon wafer is textured, a tunneling oxide layer and a doped polysilicon layer are formed on the surface. Then, a silicon nitride layer is formed on the surface of the doped layer by PECVD, and a groove is made on the surface of the silicon nitride layer. A seed layer is formed on the surface of the grooved silicon nitride layer, wherein the thickness of the silicon nitride layer is 30nm; the material of the seed layer is copper, and the thickness is 100nm. A wet film is formed on the surface of the seed layer by screen printing and cured and dried, wherein the thickness of the wet film is 10μm, the curing temperature is 80℃, and the time is 15min. The surface of the wet film after curing and drying is exposed graphically by laser direct writing, and a pattern is formed in an alkaline developer, wherein the wavelength of the light source is 325nm, and the developer is a K2CO3 solution with a concentration of 5%. Copper grid lines are electroplated on the pattern, and the width of the grid lines is 20μm and the height is 15μm. KOH is used to remove the wet film, and sulfuric acid is used to remove the seed layer.
[0104] A dielectric film layer is formed on the surface of the silicon nitride layer and the copper grid line by PECVD, wherein the dielectric film layer is silicon oxide, has a thickness of 100nm, a porosity of 30%, and a pore size of 30nm; then annealing and light injection treatment are performed, wherein the copper grid line is annealed by thermal curing, the annealing temperature is 180°C, and the time is 20min; the light injection adopts a photothermal-assisted method, and an infrared lamp is used for step-by-step light injection treatment, the first step adopts 8suns conditions for irradiation for 20s, the second step adopts 20s conditions for irradiation for 50s, and the maximum temperature is controlled at 230°C, and the third step stops the light irradiation and naturally cools to room temperature for 30s to obtain a tunnel passivated contact cell.
[0105] Comparative Example 1
[0106] The difference between Comparative Example 1 and Example 1 is that the silicon oxide dielectric film layer is replaced by a tin layer of equal thickness.
[0107] Comparative Example 2
[0108] After the silicon wafer is textured, an amorphous passivation layer and a doping layer are formed on the surface. Then, the photothermal-assisted method is used to perform step-by-step light injection with infrared laser. The first step is 8 suns for 20 seconds, the second step is 18 suns for 10 seconds, and the temperature is controlled at 180°C. The third step is 8 suns for 30 seconds, auxiliary heating, and the temperature is controlled at 230°C. The fourth step is to stop the light and cool naturally to room temperature for 60 seconds.
[0109] A transparent conductive film layer is formed on the surface after light injection treatment by PVD, and a seed layer is formed on the surface of the transparent conductive film layer, wherein the material of the transparent conductive film layer is ITO with a thickness of 30nm; the material of the seed layer is copper with a thickness of 100nm. A wet film is formed on the surface of the seed layer by screen printing and cured and dried, wherein the thickness of the wet film is 10μm, the curing temperature is 80℃, and the time is 15min. The wet film surface after curing and drying is exposed graphically by laser direct writing, and a pattern is formed in an alkaline developer, wherein the wavelength of the light source is 325nm, and the developer is a K2CO3 solution with a concentration of 5%. Copper grid lines are electroplated on the pattern, and the width of the grid lines is 20μm and the height is 15μm. KOH is used to remove the wet film, and sulfuric acid is used to remove the seed layer. Finally, the copper grid lines are annealed by thermal curing, and the annealing temperature is 180℃ for 20min to obtain a heterojunction battery.
[0110] The performance of the batteries prepared in Examples 1-4 and Comparative Examples 1-2 was tested. The test results are shown in Table 1.
[0111] Test method: The IV characteristic curve of the battery prepared by the above method was tested using the same IV tester to obtain the corresponding electrical performance parameters of open circuit voltage Voc, short circuit current Isc, fill factor FF, and conversion efficiency Eff.
[0112] Table 1
[0113] Voc(mV) <![CDATA[Isc(mA / cm 2 )]]> FF(%) Eff(%) Example 1 755 40.1 86.4 26.16 Example 2 755 40 86.3 26.06 Example 3 755 40 86.2 26.03 Example 4 748 41.2 84.5 26.04 Comparative Example 1 755 39.4 86.4 25.70 Comparative Example 2 752 39.3 85.4 25.24
[0114] According to Table 1, the heterojunction cells prepared in Examples 1-3 and the tunnel passivation contact cell prepared in Example 4 can achieve the effect of improving efficiency. Comparative Example 1 uses tin as a protective layer, but since tin itself will also oxidize and the melting point of tin is low, it cannot withstand the temperature during the light injection process, resulting in poor short-circuit current (Isc) effect; Comparative Example 2 performs light injection treatment before the transparent conductive film, but since the heterojunction cell has the characteristics of light-induced enhancement and dark annealing attenuation, the deposition of the transparent conductive film is equivalent to a dark annealing, which will cause the light injection enhancement part to decay in this process, so all electrical properties are poor.
[0115] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0116] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A solar cell, comprising a silicon substrate and a passivation contact structure stacked on at least one surface of the silicon substrate, wherein a copper electrode is provided on a partial area of the surface of the passivation contact structure, and the copper electrode forms an ohmic contact with the passivation contact structure, characterized in that: The solar cell further comprises a dielectric film layer, and the dielectric film layer is arranged on the surface of the passivation contact structure and the copper electrode.
2. The solar cell according to claim 1, characterized in that The dielectric film layer satisfies at least one of the following conditions: (1) The thickness of the dielectric film layer is 30nm-100nm; (2) The dielectric film layer is at least one layer selected from a silicon nitride layer, a silicon oxide layer, and a silicon oxynitride layer; (3) The porosity of the dielectric film layer is 30%-70%, and the pore size is 30nm-80nm.
3. The solar cell according to claim 1, characterized in that A transparent conductive film layer is also provided on the surface of the passivation contact structure, the copper electrode is arranged on a partial area of the surface of the transparent conductive film layer, the copper electrode forms an ohmic contact with the transparent conductive film layer, and the dielectric film layer is arranged on the surface of the transparent conductive film layer and the copper electrode.
4. The solar cell according to claim 3, characterized in that: The transparent conductive film layer satisfies at least one of the following conditions: (1) The thickness of the transparent conductive film layer is 30nm-50nm; (2) The material of the transparent conductive film layer is selected from at least one of indium tin oxide, indium zinc oxide, indium tungsten oxide, and stannous oxide.
5. The solar cell according to claim 3 or 4, characterized in that: The solar cell comprises a silicon substrate, wherein the silicon substrate has a light-receiving surface and a backlight surface which are arranged opposite to each other, wherein the light-receiving surface comprises an intrinsic amorphous silicon layer, an N-type doped layer, and a transparent conductive film layer which are stacked from the inside to the outside, and the backlight surface comprises an intrinsic amorphous silicon layer, a P-type doped layer, and a transparent conductive film layer which are stacked from the inside to the outside; A copper electrode is provided in a partial area on the surface of the transparent conductive film layer, and the copper electrode forms an ohmic contact with the transparent conductive film layer. The dielectric film layer is arranged on the surface of the transparent conductive film layer and the copper electrode.
6. A method for preparing a solar cell, characterized in that: The steps include: Passivating and doping the silicon wafer to form a passivated contact structure, and then preparing a copper electrode on the passivated contact structure; A dielectric film layer is prepared on the surface of the copper electrode, and then annealing and light injection treatment are performed to obtain a solar cell.
7. The method for preparing a solar cell according to claim 6, characterized in that: The dielectric film layer satisfies at least one of the following conditions: (1) The thickness of the dielectric film layer is 30nm-80nm; (2) The dielectric film layer is at least one layer selected from a silicon nitride layer, a silicon oxide layer, and a silicon oxynitride layer.
8. The method for preparing a solar cell according to claim 6, characterized in that: A transparent conductive film layer is first deposited on the passivation contact structure, and then a copper electrode is prepared, wherein the transparent conductive film layer satisfies at least one of the following conditions: (1) The thickness of the transparent conductive film layer is 30nm-50nm; (2) The material of the transparent conductive film layer is selected from at least one of indium tin oxide, indium zinc oxide, indium tungsten oxide, and stannous oxide.
9. The method for preparing a solar cell according to claim 6 or 8, characterized in that: The light injection treatment adopts a photothermal assisted method, wherein the light source is an infrared laser, the light intensity is 8 suns-40 suns, and the time is 25s-180s.
10. The method for preparing a solar cell according to claim 9, characterized in that: The light injection process includes a first light injection step, a second light injection step, a third light injection step, and a fourth cooling step, and the light injection process satisfies at least one of the following conditions: (1) The light intensity of the second light injection step is greater than the light intensity of the first light injection step, and the light intensity of the second light injection step is greater than the light intensity of the third light injection step; (2) The time of the second light injection step is shorter than the time of the first light injection step, and the time of the second light injection step is shorter than the time of the third light injection step; (3) The temperature of the second light injection step is greater than the temperature of the third light injection step.
11. The method for preparing a solar cell according to claim 10, characterized in that: The light injection process satisfies at least one of the following conditions: (1) The light intensity of the first step light injection is 8 suns-18 suns, and the time is 5s-20s; (2) The light intensity of the second light injection is 18 suns-40 suns, the time is 1 s-10 s, and the temperature is 180°C-260°C; (3) The light intensity of the third step light injection is 8 suns-18 suns, the time is 10 s-60 s, and the temperature is 160°C-240°C; (4) The cooling time in the fourth step is 10s-60s.
12. A photovoltaic module, characterized in that: Comprising the solar cell according to any one of claims 1 to 5.